2018
DOI: 10.1016/j.ccr.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Ni(0) complexes

Abstract: With its 3d 10 valence electron configuration Ni(0) is isoelectronic with Cu(I). While many Cu(I) complexes emitting from metal-to-ligand charge transfer (MLCT) excited states have been explored, the number of luminescent Ni (0) complexes known to date is very limited. Ni(0) is typically stabilized by carbonyls, phosphines or isocyanides due to the -acceptor properties of these ligands, and photoluminescence has been reported in a few selected cases that are reviewed herein. Recent studies indicate that chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Following these approaches, Ru II , Cr III , and Fe((III), low spin) complexes with strongly σ‐donating tridentate ligands have been shown to have dramatically longer emission lifetimes. Another popular strategy to induce emission in 1 st row transition metals is to use d metal‐ions to avoid non‐emissive d‐d transition, for example, Cu I , Ni 0 , and Zn II ; however, their MLCT excited states often undergo strong geometrical distortion and non‐radiative relaxation to the ground state can be rapid. Recently, Wenger and Gray et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following these approaches, Ru II , Cr III , and Fe((III), low spin) complexes with strongly σ‐donating tridentate ligands have been shown to have dramatically longer emission lifetimes. Another popular strategy to induce emission in 1 st row transition metals is to use d metal‐ions to avoid non‐emissive d‐d transition, for example, Cu I , Ni 0 , and Zn II ; however, their MLCT excited states often undergo strong geometrical distortion and non‐radiative relaxation to the ground state can be rapid. Recently, Wenger and Gray et al.…”
Section: Methodsmentioning
confidence: 99%
“…[3] Many strategies have been used to improve the photophysical properties of these complexes with the most popular focusing on the manipulation of the energies of non-emissive 3 MC states relative to emissive triplet metal-to-ligand charge transfer ( 3 MLCT) states. Following these approaches,Ru II , [5,6] Cr III , [7] and Fe((III), low spin) [8] complexes with strongly s-donating tridentate ligands have been shown to have dramatically longer emission lifetimes.A nother popular strategy to induce emission in 1 st row transition metals is to use d [10] metal-ions to avoid nonemissive d-d transition, for example,Cu I , [9] Ni 0 , [10] and Zn II ; [11] however, their MLCT excited states often undergo strong geometrical distortion [12] and non-radiative relaxation to the ground state can be rapid. Following these approaches,Ru II , [5,6] Cr III , [7] and Fe((III), low spin) [8] complexes with strongly s-donating tridentate ligands have been shown to have dramatically longer emission lifetimes.A nother popular strategy to induce emission in 1 st row transition metals is to use d [10] metal-ions to avoid nonemissive d-d transition, for example,Cu I , [9] Ni 0 , [10] and Zn II ; [11] however, their MLCT excited states often undergo strong geometrical distortion [12] and non-radiative relaxation to the ground state can be rapid.…”
mentioning
confidence: 99%
“…[4] Some fruitful approaches to destabilize the energy of the 3 MC states consist of a) introduction of strong donor ligands and b) the use of tridentate ligands that form 6-membered chelate rings to reduce the steric strain and achieve am ore octahedral geometry compared to those bearing five-membered chelate rings. Following these approaches,Ru II , [5,6] Cr III , [7] and Fe((III), low spin) [8] complexes with strongly s-donating tridentate ligands have been shown to have dramatically longer emission lifetimes.A nother popular strategy to induce emission in 1 st row transition metals is to use d [10] metal-ions to avoid nonemissive d-d transition, for example,Cu I , [9] Ni 0 , [10] and Zn II ; [11] however, their MLCT excited states often undergo strong geometrical distortion [12] and non-radiative relaxation to the ground state can be rapid. Recently,W enger and Gray et al observed 3 MLCT emission of earth abundant low-valent Cr 0 , [13] Mo 0 , [14] and W 0 [15] complexes with arylisocyanide ligands.…”
mentioning
confidence: 99%
“…Ni(II) and Co(II) complexes with dihydrazide‐based ligands were reported to be active triplet PSs for the generation of 1 O 2 , which is attractive for potential applications in PDT [68] . Moreover, Ni(0) complexes with a variety of organic ligands have been studied for their luminescence properties, which make them promising candidates for future photosensitising applications [69] . These are predominately with monodentate ligands where the luminescence is found to originate from MLCT transitions.…”
Section: Examples Of First‐row Transition‐metal Photosensitisersmentioning
confidence: 99%
“…[68] Moreover, Ni(0) complexes with a variety of organic ligands have been studied for their luminescence properties, which make them promising candidates for future photosensitising applications. [69] These are predominately with monodentate ligands where the luminescence is found to originate from MLCT transitions. Lastly, a potential V(V) PS was identified, with strong absorption in the visible region of the spectrum.…”
mentioning
confidence: 99%